2021
DOI: 10.1186/s13690-021-00626-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between opioids, environmental, demographic, and socioeconomic indicators and COVID-19 mortality rates in the United States: an ecological study at the county level

Abstract: Background The spread of the COVID-19 pandemic throughout the world presents an unprecedented challenge to public health inequities. People who use opioids may be a vulnerable group disproportionately impacted by the current pandemic, however, the limited prior research in this area makes it unclear whether COVID-19 and opioid use outcomes may be related, and whether other environmental and socioeconomic factors might play a role in explaining COVID-19 mortality. The objective of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…14 out of 164 papers included this criterion in their analysis on state, county, and city scales. The result of our review showed that the urban population in France ( Pilkington et al, 2021 ; Tchicaya et al, 2021 ), Iran ( Ramírez-Aldana et al, 2020 ), Bangladesh ( Alam, 2021 ), and the US ( Qeadan et al, 2021 ) increased the number of cases. However, reports from Italy ( Perone, 2021 ), the Netherlands ( Boterman, 2020 ), and China ( Chu et al, 2021 ) found an insignificant effect of urbanization on COVID-19 spread.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…14 out of 164 papers included this criterion in their analysis on state, county, and city scales. The result of our review showed that the urban population in France ( Pilkington et al, 2021 ; Tchicaya et al, 2021 ), Iran ( Ramírez-Aldana et al, 2020 ), Bangladesh ( Alam, 2021 ), and the US ( Qeadan et al, 2021 ) increased the number of cases. However, reports from Italy ( Perone, 2021 ), the Netherlands ( Boterman, 2020 ), and China ( Chu et al, 2021 ) found an insignificant effect of urbanization on COVID-19 spread.…”
Section: Resultsmentioning
confidence: 83%
“…On the county scale , income just appeared in the papers conducted in the US and the results seem to be contrasting. Regarding COVID-19 incidence, income was a strong and significant predictor ( Qeadan et al, 2021 ; Wheaton and Kinsella Thompson, 2020 ; Wang et al, 2021 ; Mollalo et al, 2020 ). Wheaton and Kinsella Thompson (2020) discuss that as socializing and other face-to-face activities of residents are elastic to income, there are higher cases in wealthier households.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they are at increased risk of COVID-19, and its more serious complications, due to a number of reasons ( Wang et al, 2021a ; Qeadan et al, 2021 ). Overcrowded living facilities such as shelters for the homeless, prisons, and densely-populated neighborhoods are high-risk environments for coronavirus transmission ( Wang et al, 2020 ; Kinner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ESCAPE (European study of cohorts for air pollution effects) also found the risk of all types of lung cancer increased by 22% with a 10 μg/m 3 increase in PM10 and lung adenocarcinoma by 18% with a 5 μg/m 3 increase in PM2.5 [ 11 , 12 ]. In a cross-sectional COVID-19 study, Qeadan F. et al even found that higher average daily PM2.5 exposure is positively associated with higher county-level COVID-19 mortality rates based on data of 3142 counties across the U.S. [ 13 ]. This is not the only cause; a meta-analysis for the risk factors of Chinese lung cancer rate from 2006 to 2016 revealed air pollutants, history of respiratory disease, smoking and alcohol abuse are the most important risk factors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%